PENDIDIKAN HOLISTIK, PENGEMBANGAN KURIKULUM DAN EVALUASI PENDIDIKAN - Fadjar Adji Nuryanto; Kholid Mawardi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Miller, describes three basic principles of holistic education: connectedness, inclusion, and balance. Connectedness refers to a shift from a fragmented approach to curriculum to one that seeks to facilitate connections at every level of learning. Some of these connections include integrating analytical and intuitive thinking, connecting the body and mind, integrating subjects, connecting to the community, providing a link to the earth, and connecting to the soul and spirit. The theory of "The Courage to Teach" is a concept developed by Parker J. Palmer, an American author, educator, and activist, which emphasizes that effective teaching is rooted in the teacher's personal identity, self-integrity, and ability to be open to new possibilities. The "Whole Child Approach" theory is an educational philosophy that focuses on the holistic development of children, encompassing aspects such as physical health, safety, engagement in learning, emotional support, and cognitive and social challenges, rather than solely focusing on academic achievement. Authentic character-based assessment is the assessment of students' character development through observation and measurement of actual performance in learning activities relevant to everyday life.